(3UMjM GdHNGQjs - (3GdHNGQj, GdLYaj, CHh YHO Gddg, eMeO Hf ESeGYjd Hf EHQGgje, J (B256(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; (B: (3HGH (B: (3cja cGf HOD (B( (3cPG (B) (3GdhMj Edi QShd Gddg Udi Gddg Ydjg hSde hbhd Gddg JHGQc hJYGdi (B: {(3pEnqfG nCrhnMrjnfG pEndrjnc ncneG nCrhnMrjnfG pEndi ofhmM nhGdnqfpHpqjjnf perf nHrYpOpg(B} (3h MOKfG GdMejOj YHO Gddg Hf GdRHjQ, bGd(B: (3MOKfG SajGf, bGd(B: (3MOKfG jMji Hf SYjO GdCfUGQj, bGd(B: (3CNHQfj eMeO Hf EHQGgje GdJjejs
(3BNQgG (B:s
(3MOKfG YHO Gddg Hf jhSa, MOKfG GddjK, bGd(B: (3KfG SYjO GdebHQj, Yf CHjg, Yf CHj gQjQI QVj Gddg Yfg, bGd(B: (3HjfeG fMf aj GdeSLO, NQL GdfHj Udi Gddg Ydjg hSde abGd(B: (S0(3GfWdbhG Edi GdjghO(S1 (3, aNQLfG MJiFfG HjJ GdeOQGS abGd(B: (S0(3CSdehG JSdehG, hGYdehG Cf GdCQV ddg hQShdg, hEfj CQjO Cf CLdjce s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 34s
(3eYLe GdeDdajf (B3 / 130s
(3cTa GdXfhf (B1 / 541s
(3TPQGJ GdPgH (B2 / 132s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs